E-business value creation in Small and Medium Enterprises: a US study using the TOE framework. (4th January 2010) - Wen, Kuang-Wei; Chen, Yan
This research intended to identify the factors of and their impacts on e-business value creation in Small and Medium Enterprises (SMEs). We followed the Technology-Organisation-Environment (TOE) theory of innovation diffusion and drew heavily upon Zhu et al. (2004) in developing a causal model for SMEs. The model was validated using data obtained from a survey of SMEs in an upper Midwestern metropolitan area. Our results supported the hypotheses that technology readiness and competition intensity have positive impact, and firm size has negative effect on e-business value. However, we also found that SMEs' financial resource appropriation for IT and regulatory environment had no impact on e-business value.